Simultaneous Determination of Amphenicols and Metabolites in Animal-Derived Foods Using Ultrahigh-Performance Liquid Chromatography-Tandem Mass Spectrometry - Xinyi Wu; Xixi Shen; Xiangyue Cao; Rongrong Nie; Haonan Zhang; Changbo Tang; Wei Wang (International Journal of Analytical Chemistry)
Amphenicols are widely used to prevent and treat animal diseases. However, amphenicol residues accumulate in livestock and poultry and harm consumers. We hypothesized that one can combine solid-phase extraction (SPE) with ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to simultaneously determine amphenicols and metabolites in pork, beef, lamb, chicken, and their products and meet government regulations for maximum residue limits. We extracted crude samples with ethyl acetate and ammonia water (98:2, v/v), purified the samples with a CNW Si SPE column, defatted the samples with acetonitrile-saturated n-hexane, and then determined the resulting analytes by UHPLC-MS/MS. The limit of detection of the analytes in livestock and poultry meat was 0.03–1.50 μg/kg, and the limit of quantification was 0.05–5.00 μg/kg. Measured chloramphenicol, thiamphenicol, and florfenicol concentrations were linear over the range 0.50–50 μg/kg; and the florfenicol amine concentration was linear over the range 5.00–200 μg/kg (all with correlation coefficients >0.9990). The recovery of the spiked samples was between 72% and 120%. The intraday relative standard deviation (RSD) ranged from 1% to 9%, and the interday RSD ranged from 1% to 12%. Based on the above results, the current method is sensitive, accurate, and reproducible with the detection limits being well below the maximum residue limits as per Chinese standard GB 31650-2019, and thus, our research hypothesis could be confirmed.